STUDI KOMPARASI PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENTS) DAN PEMBELAJARAN KONVENSIONAL TERHADAP HASIL BELAJAR KOMPETENSI MEMAHAMI DASAR-DASAR MESIN - Zuhdi, Mukhamad Ali (Journal of Mechanical Engineering Learning, 2014)
This study aimed to determine differences in student learning outcomes to understand the basics of competency using cooperative learning machine TGT (Team Games Tournaments) with conventional learning and to determine student learning outcomes in the competence to understand the basics of the engine between cooperative learning TGT (Team Games Tournaments) with conventional learning . This study used an experimental method with pre-test pattern post -test control group design . The population of this research were 96 students from three classes in vocational X TKR SMK Darussalam Balapulang which take competence to understand the basics of the machine. Determination of the study sample stratified random sampling technique, X TKR 1 as the experiments class and class X TKR 2 as the control class. Collecting data using methods of documentation, observation methods and test methods. Data analysis using statistical descriptions and t test. Competency learning outcomes to understand the basics of the machine in class X TKR SMK Darussalam Balapulang using cooperative learning TGT (Teams Games Tournaments) better than conventional learning.